INTEGRATION OF SMART GRID SYSTEMS AND GEOINFORMATION TECHNOLOGIES: CHALLENGES AND OPPORTUNITIES - Azizbek Temirov; Ernazar Reypnazarov; Shakhlo Khujamatova; Abror Isakov (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, in the application of geo-information technologies for Smart Grid, in the design and determination of route schedules for energy companies located in geographical and population-friendly places, choosing the most optimal option for construction, the rational use and status of centralized energy sources in the design of new energy supply systems by companies, it is very useful to gather enough information about them. The development of web portals, navigation systems and mobile phone applications on the Internet has paved the way for ordinary citizens. This article describes the application of geo-information technologies to problems aimed at improving their functions for the Smart grid implemented in the geographic information system.